Examination of Doubts of Woman’s Character from the Viewpoint of Orientalists - Golizad Bahari, Nahid; Safari, Ali; Ali Mahdawi Rad, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
God has chosen man as his own deputy on earth and the noblest of all creatures and dignified him. According to the verses of Holy Quran, man has been created in two sexes, i.e. male and female. Quranic verses insist on the idea that no one of the two sexes has any essential nobility and dignity over the other and God wariness is introduced as the measure of human value. However, some orientalists by a superficial reading of the Quran underline such issues as the guardianship of man, divorce and etc., and consider the woman to be of a second-degree human value and a weak creature in Quran. Having said these, they seek to challenge the authority of Quran and describe it as a book written by a man. The present essay by a descriptive-analytic method and by the study and criticism of doubts and objections casted by the orientalists, based on the divine verses and Islamic doctrines has proceeded to defend the place of woman and truthfulness of Quran. It is concluded that the doubts casted by the orientalists are due to the lack of awareness or misunderstanding and lack of comprehensive knowledge of all aspects of Quran and Islam or in some cases, out of animosity and fight with Islam.